Distributed electrical power production system based on HVDC network and AC looped netowrk - GONG YI; QIU XIAOYONG (2016)
The utility model discloses a distributed electrical power production system based on HVDC network and AC looped netowrk, it contains the HVDC network, AC looped netowrk, mains network, power conversion equipment, communication link, ammeter equipment, power conversion equipment is two -way power conversion equipment, communication link is two -way communication link, ammeter equipment is two -way ammeter equipment, two -way power conversion equipment includes two -way ACAC electric energy transducer, two -way DCAC electric energy transducer, two -way ACDC electric energy transducer, the both -way communication link is two -way wired communication link, or two -way wireless communication link, or two -way wired communication link and two -way wireless communication link's combination, two -way ammeter equipment is used for carrying out periodic statistics to the electric energy of bidirectional flow warp. 本实用新型公开了种基于HVDC网络与AC环网的分布式发电系统，其包含HVDC网络，AC环网，市电网络，电能转换设备，通信链路，电表设备；所述电能转换设备为双向电能转换设备，所述通信链路为双向通信链路，所述电表设